Effect of the Hydroethanolic Extract of Bixa orellana Linn (Bixaceae) Leaves on Castor Oil-Induced Diarrhea in Swiss Albino Mice - Michel Archange Fokam Tagne; Hypolyte Akaou; Paul Aimé Noubissi; Angèle Foyet Fondjo; Yaouke Rékabi; Henri Wambe; René Kamgang; Jean-Louis Essame Oyono (Gastroenterology Research and Practice)
Objective. The treatment of diarrheal diseases is a serious problem in developing countries, where population generally uses medicinal plants. The leaves of Bixa orellana have been reported to be traditionally used in the treatment of diarrhea by local people in the district of Khulna in Bangladesh. The aim of this study was to investigate the effects of the hydroethanolic extract of Bixa orellana leaves on castor oil-induced diarrhea in mice. Methods. The powder of the leaves of Bixa orellana was macerated in ethanol/water mixture (20/80) for 48 hours and then filtered. The filtrate obtained was lyophilized, and the solutions to be administered to the animals were prepared. To induce diarrhea, animals orally received castor oil (1 mL/100 g bw). To determine the effective doses, each mouse received, 30 minutes after the administration of castor oil, one of the single oral doses of hydroethanolic extract of Bixa orellana leaves: 0, 25, 50, 100, and 200 mg/kg bw. The mass, number, and frequency of stool diarrhea were measured and recorded per hour for five hours. The effect of the hydroethanolic extract of Bixa orellana leaves on the intestinal transit was evaluated by measuring the distance traveled by the charcoal meal in thirty minutes. The effects of the aqueous extract of hydroethanolic extract of Bixa orellana leaves on intestinal secretion were evaluated by measuring the volume of the intestinal content and by dosing the electrolytes (Na+, K+, and Cl-) in the intestinal content by the colorimetric method. Results. The extract produced significant (P<0.01) decreases, respectively, 35.52%, 54.47%, 74.80%, and 87.80% in the severity of diarrhea. The extract at 100 and 200 mg/kg bw showed a significant (P<0.01) decrease of castor oil-induced enteropooling (61.08% and 65.41%), and only the 200 mg/kg bw exhibited significant (P<0.01) reduction on intestinal transit (24.46%) as compared to standard drug. Conclusions. The hydroethanolic extract was found to be effective against castor oil-induced diarrhea in experimental mice at 50, 100, and 200 mg/kg bw which provides evidence that could justify its traditional use.